Appraising Intellectual Giftedness Using the Malay Version of WISC-R - Mohd Isa, Abd Majid; Mohamed, Othman (Universiti Putra Malaysia Press, 1995)
An appropriateness study of the Malay version of the WISC-R was conducted on one hundred 11 year old students (53 boys and 47 girls). Prior to the study, the WISC-R was systematically translated using the back translation method with a panel of experts as moderators. From the results of the study, the reliability index of the Malay version of the WISC-R is .91 and this coefficient is consistent with the condition set for an individual standardised test. The score for each sub-tests too does not differ from the data presented by the original WISC-R. Therefore, the Malay version of WISC-R is appropriate for use as a measure of intelligence (IQ).